Prevalência de diabetes mellitus e tolerância à glicose diminuída na população urbana de 30 a 79 anos da cidade de São Carlos (São Paulo) - Bosi, Paula Lima (2009)
Objective: To assess the prevalence of diabetes (DM) and impaired glucose tolerance (IGT) in the urban population aged 30-79 years of the city of São Carlos (SP), Brazil. Methods: It was performed a cross-sectional population survey, from August 2007 to June 2008. Subjects were first screened by fasting capillary glucose. Non diabetic individuals were administered a 75g oral glucose tolerance test and classified as diabetic, glucose intolerant or nondiabetic according to World Health Organization recommendations. Results: 1116 individuals participated, 65% female and 35% male. The overall rates of DM and IGT were 13,5% and 5%, respectively. DM and IGT were associated with age, education and obesity. However they were not associated with gender, race or income. Conclusion: The prevalence of DM has increased when compared with previous studies in Brazil and in the state, thus confirming the national and world expectations.